Walnut protein isolate antibacterial biological membrane as well as preparation method and application thereof
Through the complexation of WNPI and PGA and the combination of CA, a walnut protein bio-anti-bacterial membrane with antibacterial, antioxidant and oxygen barrier capabilities was prepared, which solved the shortcomings of protein functional improvement in the prior art, and achieved the effect of extending the shelf life of food and improving the performance of packaging materials.
Patent Information
- Application Number
- CN202510055669.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2045-01-14
AI Technical Summary
The prior art has shortcomings in improving protein functionality, especially the instability of heat treatment, and few studies on the aggregation of protein isolates and polysaccharides in walnuts.
Through the complexation of WNPI and PGA, internal and external factors are adjusted to prepare a composite coagulant with a predetermined function and combined with CA to make a bio-anti-bacterial membrane.
The antibacterial, antioxidant and oxygen barrier properties of walnut protein bioanti-anti-bacterial membrane are achieved, extending the shelf life of food, and improving the performance of packaging materials.
Smart Images

Figure CN119661883A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of antibacterial biofilms, and in particular to a walnut protein isolate antibacterial biofilm and a preparation method and application thereof. Background Art
[0002] WNPI (walnut protein isolate) is the main protein component in walnut meal, but its solubility is poor, which limits its application in food processing. At present, many studies have adopted physical, chemical and biotechnological methods to improve the functionality of proteins. Among them, pH induction and thermal induction are two traditional and simple techniques that are widely used to improve protein functions. For example, Jeong et al. reported that pH induction can significantly improve the water retention and gelling properties of pea protein. However, these methods, especially heat treatment, still have many shortcomings. As an emerging technology, the coagulation of protein and polysaccharide has attracted widespread attention due to its high loading capacity, high encapsulation efficiency, high thermal stability and complex structure, and can achieve sustained release of core materials. At present, there are few studies on the coagulation of WNPI and polysaccharides.
[0003] Therefore, the present invention proposes a composite of WNPI and PGA to improve the functional properties of WNPI near the isoelectric point. PGA is a low-cost natural amphiphilic polysaccharide widely used in beverages and jams. The performance of its complex can be improved through electrostatic interaction with WNPI. The study will explore the electrostatic complex mechanism of the interaction between PGA and WNPI under specific conditions, and purposefully prepare complex coacervates with predetermined functions by adjusting internal (pH value, ionic strength and biopolymer ratio) and external factors (temperature). In addition, in view of the antioxidant and antibacterial properties of chlorogenic acid, as well as its environmental sensitivity and easy degradation, the present invention will also explore the use of WNPI / PGA complex coacervates as its encapsulation carrier to enhance the stability of the encapsulated material. Summary of the invention
[0004] In view of the shortcomings of the prior art, the present invention provides a walnut protein isolate antibacterial biofilm and a preparation method and application thereof; the present invention adopts WNPI / PGA composite as a wall material to fix CA (chlorogenic acid), and then combines it with PVA (polyvinyl alcohol) to prepare a biological antibacterial film. The walnut protein biological antibacterial film provided by the present invention has strong antibacterial, antioxidant and oxygen barrier capabilities.
[0005] In order to solve the above technical problems, the technical solution of the present invention is as follows:
[0006] In a first aspect, the present invention provides a method for preparing a walnut protein isolate antibacterial biofilm, the preparation method comprising the following steps:
[0007] Step (1) mixing a WNPI stock solution and a PGA stock solution, stirring to prepare a WNPI / PGA complex coacervate;
[0008] Step (2) slowly adding the CA stock solution into the WNPI-PGA complex coacervate solution, stirring in the dark to obtain the WNPI / PGA-CA complex coacervate;
[0009] Step (3) The PVA solution and the WNPI / PGA-CA complex coacervate are mixed and stirred at room temperature, refrigerated overnight, and then dried and cooled, and then balanced in a dryer to obtain a walnut protein isolate antibacterial biofilm.
[0010] Preferably, the mass ratio of WNPI to PGA is 1.5-3:1, and the total concentration of the two in the reaction system reaches 0.4-1.0% (w / v).
[0011] Preferably, the mass ratio of WNPI / PGA to CA is 2-8:1; further preferably, the mass ratio of WNPI / PGA to CA is 3-6:1.
[0012] The concentration of CA in the CA stock solution is 0.3-1.0% (w / v); the CA stock solution is slowly added to the WNPI-PGA complex coacervate solution to adjust the final concentration of CA to 0.05%-0.20% (w / v).
[0013] Preferably, in step (1), 0.5-1.5 mol / L hydrochloric acid is used to adjust the pH of the reaction system to 3.0-6.0; and the reaction temperature is 2-8°C.
[0014] Preferably, in step (2), the pH of the mixed solution is adjusted to 3.0-6.0 using 0.5-1.5 mol / L hydrochloric acid, followed by stirring for 20-60 minutes in the dark, and then low-speed centrifugation at 2500-4000 rpm for 8-20 minutes to remove possible large aggregates and undissolved matter.
[0015] Preferably, glycerol and Tween-80 are further added to the reaction system in step (3); the concentration of glycerol in the reaction system is 0.5-1.0%; the concentration of Tween-80 in the reaction system is 0.05-0.2%; the concentration of the PVA solution is 3-10% (w / v); and the mass ratio of PVA, WNPI / PGA-CA, glycerol and Tween-80 is 3-10:0.3-1.0:0.5-1.0:0.05-0.2.
[0016] The second aspect of the present invention also provides a walnut protein isolate antibacterial biofilm prepared by the method.
[0017] The third aspect of the present invention further provides the use of the walnut protein isolate antibacterial biofilm in the preparation of antioxidants or antibacterial agents.
[0018] The fourth aspect of the present invention further provides the use of walnut protein isolate antibacterial biofilm in the preparation of food preservatives or food packaging bags.
[0019] Preferably, the food is meat products, fruit, yogurt or jelly.
[0020] The characteristics of the present invention are as follows: the WNPI-PGA complex still retains a certain net negative charge during the complex process, and the repulsion in the system is sufficient to resist the aggregation of the complex. The mass ratio of protein to polysaccharide is another key factor affecting the complex coagulation process. Different mass ratios will affect the charge balance between the two, and then affect their interaction and complex strength. In the present invention, when the ratio of WNPI-PGA is preferably 2:1, WNPI saturates the adsorption of PGA sugar chains, and the insoluble coagulants of WNPI-PGA reach a maximum value, showing that increasing the polysaccharide concentration can effectively inhibit further aggregation of proteins. After WNPI and PGA form a coagulant, the molecular structure of the WNPI protein undergoes changes, and the thermal stability of the coagulant is improved due to the addition of polysaccharides. This enhancement may be due to the formation of a large number of hydrogen bonds during the coagulation process, making the crystal structure more stable and ordered, and forming a dense lamellar structure. These findings indicate that WNPI-PGA coagulants are ideal for encapsulating and preserving bioactive compounds, and are suitable for controlled release and targeted delivery.
[0021] In order to enhance the stability of CA, the present invention selects WNPI / PGA complex coacervate as the carrier material of freeze-dried nanoparticles. The particle size, PDI and surface charge of nanoparticles are key indicators for evaluating their long-term stability and controlled release behavior. Studies have shown that compared with WNPI / PGA:CA12:1, the particle size of WNPI / PGA:CA6:1, WNPI / PGA:CA4:1 and WNPI / PGA:CA3:1 is significantly increased. This change may be due to the increase in the amount of CA added, which significantly enlarges the size of the nanoparticles. The surface electrostatic charge of the composite nanoparticles decreases, which may be due to the decrease in the Zeta-potential of free protein and polysaccharide molecules and protein-polysaccharide complexes in the solution. It is speculated that this is because the increase in the chlorogenic acid content in the system may inhibit the potential reaction. The water contact angles of the composite nanoparticles are all less than 90°, showing good hydrophilicity, which may be the result of chlorogenic acid inhibiting the hydrophobicity of the protein surface. Therefore, WNPI / PGA:CA4:1 has become a preferred solution for nanoparticles due to its excellent hydrophilicity and stable structure.
[0022] In terms of encapsulation efficiency (EE) and loading capacity (LC), WNPI / PGA:CA4:1 The WNPI / PGA:CA nanoparticles have a higher EE than the other CA nanoparticles, which is 92.30% and 18.46% respectively. This may be because the WNPI molecules have more sites for binding with CA. In addition, the addition of PGA increases the viscosity of the continuous phase, thereby inhibiting the migration of CA to a certain extent, which is manifested as a higher EE. 4:1 The delivery system is considered to be an ideal carrier for further application of CA in food processing due to its high encapsulation capacity. 4:1 The nanoparticles are also significantly superior to the other four groups of nanoparticles in terms of thermal stability, freeze-thaw resistance, pH stability, temperature storage stability and light stability.
[0023] In order to improve the stability of CA, WNPI / PGA composite was used as a wall material to fix CA, and then combined with PVA to make a film, aiming to develop packaging materials that can extend the shelf life of foods such as meat products. Compared with pure PVA film without nanoparticles, the film containing nanoparticles has an increased thickness due to the increase in mass after solution casting. Generally, the barrier properties of a film are directly affected by the composition of its substrate. The results show that the water vapor permeability (WVP) of the walnut protein antibacterial film is maintained at a low level. The addition of CA slightly improves the WVP of the film. At the same time, the addition of glycerol, a hydrophilic plasticizer, can improve certain physical properties of the composite film, such as flexibility, water solubility and WVP. Taking all factors into consideration, the composite film containing CA has excellent barrier properties, proving that the walnut protein antibacterial film is suitable for packaging materials. The transmittance of the composite film after CA addition is significantly reduced, which is due to the absorption of ultraviolet light by CA. Studies have shown that this composite film can effectively block ultraviolet rays and is suitable for food packaging. As the content of WNPI / PGA-CA increased, the free radical scavenging ability and antioxidant capacity of the film increased significantly, and all samples showed dose-dependent antioxidant properties. In addition, the PVA-based film loaded with WNPI / PGA-CA showed antibacterial effects against Staphylococcus aureus and Escherichia coli, indicating its potential as an active food packaging material.
[0024] In view of the fact that meat products are susceptible to microbial contamination and spoilage, changes in the storage environment may also trigger fat oxidation. The present invention mixes WNPI / PGA-CA with PVA to prepare a PVA-WNPI / PGA-CA packaging film, and applies it to the antioxidant, antibacterial and fresh-keeping of meat products. Studies have shown that the addition of PVA-WNPI / PGA-CA significantly prolongs the shelf life of pork and slows down changes in appearance quality. Therefore, adding WNPI / PGA-CA nanoparticles to the packaging matrix can effectively prolong the shelf life of food, and the present invention can provide a certain theoretical basis for the application of WNPI / PGA-CA nanoparticles in food packaging.
[0025] Compared with the prior art, the present invention has the following beneficial effects: After the WNPI / PGA-CA suspension is mixed with the PVA solution, the PVA-WNPI / PGA-CA composite film is prepared by a casting method. Studies have shown that as the WNPI / PGA-CA ratio increases, the surface roughness and thickness of the film increase, the tensile strength increases, and the elongation at break decreases. In particular, the tensile strength of the PVA-WNPI / PGA-CA film is higher than that of the pure PVA film, and the elongation at break decreases, which is attributed to the hydrogen bonds and electrostatic interactions formed between WNPI / PGA-CA and the film matrix, which increase the viscosity of the film-forming liquid, thereby improving the mechanical properties of the film. After adding WNPI / PGA-CA, the water vapor permeability (WVP) and oxygen permeability (OP) of the film are both reduced. At the same time, the ultraviolet-visible light barrier ability, antibacterial and antioxidant ability of these films are also significantly enhanced. In the process of food preservation, the PVA-WNPI / PGA-CA film exhibits strong antibacterial, antioxidant and oxygen barrier abilities. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The morphological photographs of WNPI-PGA complex coacervates (5000×) taken by scanning electron microscopy (SEM) are shown. Figures A, B, and C correspond to the complex coacervates generated at pH values of 2.5, 3.5, and 6.0, respectively. Figures D, E, and F correspond to the complex coacervates formed after adding 5mM, 10mM, and 20mM NaCl. Figures G, H, and I represent the complex coacervates when the ratio of WNPI to PGA is 1:1, 2:1, and 1:2;
[0027] Figure 2 for WNPI, WNPI / PGA:CA 12:1 ,WNPI / PGA:CA 6:1 ,WNPI / PGA:CA 4:1 and WNPI / PGA:CA 3:1 Water contact angle;
[0028] Figure 3 WNPI / PGA:CA 12:1 ,WNPI / PGA:CA 6:1 ,WNPI / PGA:CA 4:1 and WNPI / PGA:CA 3:1 The influence of EE and LC in CA;
[0029] Figure 4 Cross-sectional SEM images of (A) PVA film, (B) PVA-CA film, (C) PVA--WNPI / PGA-CA I film, (D) PVA--WNPI / PGA-CAII film, and (E) PVA--WNPI / PGA-CA III film;
[0030] Figure 5 are the tensile strength (A) and elongation at break (B) of the antibacterial film;
[0031] Figure 6 is the viscosity of the film-forming liquid;
[0032] Figure 7 This is the appearance of the antibacterial film;
[0033] Figure 8 is the light transmittance of the antibacterial film;
[0034] Fig. 9 (A) DPPH and (B) ABTS free radical scavenging rates of the antibacterial films;
[0035] Fig.10 The absorbance of bacterial suspension treated with film-forming liquid: (A) Escherichia coli, (B) Staphylococcus aureus;
[0036] Fig.11 The effect of different packaging films on the pH value of pork samples;
[0037] Fig.12 To study the effect of different packaging films on the production of volatile basic nitrogen in pork samples during storage;
[0038] Fig.13 is the total number of colonies in each group of pork during storage. DETAILED DESCRIPTION
[0039] The technical solution of the present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments, but the present invention is not limited to the following technical solution.
[0040] Example 1
[0041] Preparation of walnut protein isolate
[0042] The walnut meal was crushed, dried at 45-48°C to constant weight, sieved with 150 mesh, and the walnut meal was mixed with n-hexane at a ratio of 1:5 (w / v) for degreasing. Constant magnetic stirring was used for 2 hours, and then filtered and the residue was collected. The degreasing process was repeated until the filtrate became colorless and transparent. The defatted residue was placed in a fume hood to evaporate the residual solvent. The dried residue was then crushed in a grinder and sieved (200 mesh) to obtain defatted walnut meal powder. This powder was stored in a refrigerator at 4°C.
[0043] The defatted walnut meal powder was mixed with water in a ratio of 1:20 (w / v), the pH value of the solution was adjusted to 11 with 1M NaOH, constant magnetic stirring was performed for 1.5 hours, and then centrifuged (4°C, 3000 rpm, 10 min) to obtain a clear protein solution, the pH value of the supernatant was adjusted to 4.5 with 1M HCl, allowed to stand for 1 hour, centrifuged (4°C, 3000 rpm, 15 min), the precipitate was washed (with water), neutralized, the pH was adjusted to neutral (7.0), and walnut protein isolate (WNPI) was obtained by freeze-drying and stored in a brown reagent bottle at 4°C.
[0044] Preparation of WNPI-PGA composite solution
[0045] 2.00 g of WNPI powder was accurately weighed, and 100 mL of deionized water was added to dissolve to obtain a 2% (w / v) stock solution. The solution was hydrated at 4°C with a magnetic stirrer at 500 rpm for 12 h, and then the pH of the solution was adjusted and maintained at 12 using 1.0 mol / L NaOH, stirred at room temperature for 3 h, and then the pH of the solution was slowly adjusted to neutral using 0.1 mol / L HCl. The solution was centrifuged at 4500 rpm / min for 30 min to remove the insoluble components to obtain a WNPI solution. 1.00 g of PGA powder was dissolved in 100 mL of deionized water to prepare a 1% (w / v) PGA stock solution, which was stirred at 800 rpm with a magnetic stirrer at 25°C until it was completely dissolved.
[0046] Different proportions of WNPI and PGA (propylene glycol alginate) stock solutions were mixed, stirred for 2 hours, and diluted to a total biological concentration of 0.6% to prepare WNPI / PGA composite solutions. The pH value was then adjusted using NaOH and HCl solutions to perform coagulation reactions under different conditions. The interaction effects at different pH values (2.0-10.0), sodium chloride concentrations (0-40mM), proteoglycan mass ratios (1:2, 1:1, 2:1, 4:1, 10:1w / w) and temperatures (4, 25, 35, 45°C) were studied by measuring turbidity, Zeta-potential, and coagulation yield.
[0047] The present invention observed the appearance of WNPI-PGA coagulates at different pH values. The pH values at the beginning of the formation of soluble complexes, coagulates and maximum turbidity are usually expressed as pHc, and pHopt, while The pH value corresponding to the complete protonation of the charged groups of the polysaccharide and the loss of electrostatic binding ability with proteins. Critical pH value It is defined as the intersection of the two tangents of the turbidity curve. pHopt is the pH value corresponding to the maximum turbidity. When the pH is 3.5 (pHopt), the turbidity reaches a peak value of 0.946, forming an obvious insoluble complex coacervate (suitable for film formation), and the optimal reaction pH is 3.5.
[0048] In addition, in order to further understand the effect of the pH value of the mixture on the electrostatic interaction between WNPI and PGA, the present invention measured the Zeta potential and particle size of the polymer. As the pH value (from 2 to 10.0) changes, the Zeta potential of the pure WNPI solution increases from -27.83 mV to 8.22 mV, that is, pH has an effect on the surface charge of WNPI. The charge size of the ionizable groups on WNPI (especially carboxyl and amino groups) depends on the pH value. When the pH value is adjusted from far below the pKa value to far above the pKa value, the carboxyl group changes from neutral (-COOH) to completely negative (-COO-), while the amino group changes from positive (-NH 3 + ) becomes neutral (-NH 2 ). Therefore, as the pH value increases, the net charge on the protein changes from positive to negative, which means that their solubility, structure, interaction and function are all dependent on the pH value. At higher pH values, the WNPI-PGA polymer has a higher Zeta potential, indicating that the formation of the WNPI-PGA polymer is stable. As the pH value of the solution gradually decreases, the Zeta potential of the WNPI-PGA mixed solution continues to rise. Based on these findings, the present application believes that WNPI and PGA will electrostatically attract each other between pH values 2-5 because WNPI is positively charged and PGA is negatively charged within this pH range.
[0049] Effect of temperature on the behavior of WNPI-PGA complex coacervation: In order to study the effect of temperature on the interaction of WNPI-PGA complex coacervates, the phase behavior of the complex coacervates in the temperature range of 4-55℃ was analyzed, with room temperature as a control. When the temperature dropped to 4℃, the turbidity curve and critical pH value of the complex coacervates shifted to lower pH values, indicating that low temperature enhanced the effect of hydrogen bonding and promoted the formation of complex coacervates. In contrast, when the temperature increased to 25-55℃, the turbidity curve and critical pH value shifted to higher pH values due to the weakening of hydrogen bonding by high temperature, causing the coacervate structure to become unstable. Although hydrophobic interactions do not seem to have a direct effect on coacervate formation, they help stabilize the structure of the WNPI-PGA complex. In addition, high temperature also seems to promote electrostatic bonding between WNPI and PGA. Therefore, the optimal reaction temperature is around 4℃.
[0050] Effect of ionic strength on the coacervation behavior of WNPI-PGA complexes: This paper investigates the effect of different concentrations of NaCl (0, 5, 10, 20 and 40 mM) on the turbidity of WNPI-PGA mixtures in the pH range of 1.0 to 10.0. As the salt ionic strength increases, pHc and Both shifted to lower pH values, indicating that Na + With positively charged groups and Cl in proteins - Competitive adsorption occurs with the negatively charged groups in the polysaccharide side chains, interfering with the electrostatic binding between WNPI and PGA, thereby reducing the aggregation behavior of WNPI and PGA. Therefore, no additional salt ions are required.
[0051] Effect of protein / polysaccharide mass ratio on the behavior of WNPI-PGA complex coacervation: The present invention explores the pH-dependent behavior of complex coacervates when the ratio of WNPI to PGA changes from 1:2 to 10:1. As the ratio of protein to polysaccharide increases from 2:1 to 10:1, the turbidity curve moves to lower pH values and the maximum turbidity decreases, reaching the maximum at a ratio of 2:1. As the ratio increases, the pH c down to about 6.5, while (pH at the beginning of coacervate formation) remains at about 7.0. Similarly, as the ratio increases, the pH of the most significant interaction point in the mixture opt (pH value at the beginning of maximum turbidity formation) also shows similar changes. Therefore, it can be concluded that at a ratio of 2:1, the sugar chains of PGA are saturated with WNPI, and the insoluble aggregates of WNPI-PGA reach their maximum. When the polysaccharide concentration is higher than that of protein (such as 1:2), the maximum turbidity value decreases significantly, the turbidity curve shifts to the left, and the pH opt It also dropped from 0.946 to 0.152. Under conditions of high polysaccharide concentration, PGA molecules are oversaturated, resulting in a reduction in the number of amino groups of WNPI available for binding. In addition, the light scattering effectiveness of polysaccharide molecules in the protein-polysaccharide mixture is not as good as that of protein molecules. Therefore, the turbidity of the entire system dropped significantly. Such a huge difference indicates that the presence of excess PGA affects the aggregation of the resulting aggregates. This result shows that increasing the concentration of polysaccharides in the entire system can inhibit further aggregation of proteins.
[0052] Microstructure of WNPI-PGA complex coacervate: Figure 1 The microstructure of the surface of WNPI-PGA complex coacervates prepared under various conditions is shown. It is well known that the surface of native WNPI presents a complex structure consisting of random flakes of various sizes and shapes. This flake-like structure is attributed to the binding of protein molecules at high density, which affects their dispersibility and solubility. PGA, a high molecular weight polysaccharide, shows a filamentous structure with a smooth surface. Figure 1 AC shows the difference in the microstructure of the coacervate under different pH conditions. When the pH value is 6.0, its morphology is a dense lamellar structure. As the pH value decreases, a lamellar porous structure appears. It is worth noting that at pH 3.5, the surface is rough. This result further proves that the strength of electrostatic interaction is different under different pH conditions. At a lower pH value (2.5), the electrostatic interaction is stronger and the coacervate presents a denser network structure. Therefore, the macromolecules WNPI and PGA form an aggregation network due to electrostatic interactions, which complicates the cohesive structure. As the salt ion concentration increases, it is observed that the surface of the lamellar structure becomes gradually rough. In particular, when the salt ion concentration is increased to 20mM, the structure appears as irregular rough flakes. This phenomenon is attributed to the strong electrostatic shielding effect under high salt concentration, which inhibits protein aggregation and destroys the structure of the coacervate. When the mass ratio of protein to polysaccharide was 1:1 and 1:2, the surface roughness increased significantly, while at a ratio of 2:1, the surface was relatively smooth, indicating that when the ratio of WNPI to PGA was 2:1, the saturation of protein and polysaccharide was higher and the interaction intensity was the strongest, thus forming a tighter and denser network structure.
[0053] In summary, the method for preparing the WNPI-PGA complex coacervate is preferably as follows: the stock solutions of WNPI and PGA are mixed in a ratio of 2:1, and gently stirred on a magnetic stirrer for 120 minutes, and the total biopolymer concentration of the solution is adjusted to 0.6% (w / v). Subsequently, the mixed solution is acidified with 1 mol / L hydrochloric acid and the pH is adjusted to 3.5. After acidification, the sample is allowed to stand at room temperature for two days to induce phase separation of the solution, and then the bottom enriched phase is collected for later use. The enriched phase is freeze-dried by vacuum freeze drying to obtain a dry coacervate.
[0054] Preparation of CA-loaded WNPI / PGA composite nanoparticles
[0055] WNPI / PGA complex coacervates were prepared by mixing WNPI and PGA stock solutions in a ratio of 2:1 and gently stirring on a magnetic stirrer for 30-120 minutes to ensure that the total biopolymer concentration reached 0.6% (w / v).
[0056] First, accurately weigh a certain amount of CA powder, then add it to deionized water, stir at 300 rpm in the dark for 1 hour at room temperature to prepare a CA stock solution (0.5%, w / v). Slowly add this CA stock solution to the WNPI-PGA complex coacervate solution to adjust the final concentration of CA to 0.05%, 0.10%, 0.15%, and 0.20% (w / v), respectively. Use 1 mol / L hydrochloric acid to adjust the pH of the mixed solution to 3.5. After stirring in the dark for 30 minutes, the sample was centrifuged at low speed (3000 rpm, 10 minutes) to remove possible large aggregates and undissolved matter to obtain a WNPI-PGA complex coacervate containing CA (WNPI / PGA-CA). Part of the complex coacervate sample was stored at 4°C, while the other part was freeze-dried to prepare solid freeze-dried nanoparticles. Thus, the mass ratio of WNPI / PGA to CA in the final nanoparticle sample was WNPI / PGA:CA 12:1 、WNPI / PGA:CA 6:1 、WNPI / PGA:CA 4:1 and WNPI / PGA:CA 3:1 .
[0057] WNPI / PGA:CA 12:1 、WNPI / PGA:CA 6:1 、WNPI / PGA:CA 4:1 and WNPI / PGA:CA 3:1 The average diameter, polydispersity index (PDI) and zeta potential of the samples were measured at 25° C. using a dynamic light scattering electrophoresis instrument. Before the measurement, all samples were diluted with deionized water to a total biopolymer concentration of 0.1 wt %.
[0058] Characterization of WNPI-PGA aggregates self-assembled and embedded chlorogenic acid nanoparticles
[0059] Particle size and potential analysis of WNPI / PGA-CA nanoparticles
[0060] Table 1 Average particle size, Zeta potential and polydispersity index of nanoparticles loaded with different concentrations of CA (P<0.05)
[0061]
[0062] It can be seen from Table 1 that the size of the nanoparticles is medium, and it tends to increase with the increasing content of chlorogenic acid. This may be related to the formation and dissociation of WN PI / PGA electrostatic complexes. The potential reason for the increase in particle size may be that the peptides and amino acids released mainly through hydrophobic interactions during the hydrolysis process, accompanied by electrostatic attraction, electrostatic repulsion, and the exchange of thiol and disulfide bonds promote protein aggregation. PDI is an indicator for evaluating the dispersibility of high molecular polymers. PDI is generally between 0 and 1, PDI <0.3 indicates monodispersity, and PDI >0.3 indicates high polydispersity. As shown in Table 1, the nanoparticles produced by the present invention are uniform. Especially WNPI / PGA:CA 4:1 The PDI value of nanoparticles was 0.26±0.02, which was lower than that of the other three groups. Zeta potential is one of the key parameters for evaluating the stability of nanoparticles. The larger the absolute value of the Zeta potential, the more stable the nanoparticles. As shown in Table 1, the Zeta potential of all nanoparticles was lower than -19.56 mV, among which WNPI / PGA:CA 6:1 and WNPI / PGA:CA 4:1 The zeta potential of the nanoparticles was lower than that of the other two groups, indicating that they were more stable. These results indicate that the addition of an appropriate amount of CA can transform large plant protein aggregates into stable nanoparticles.
[0063] Water contact angle of WNPI / PGA-CA nanoparticles: This example measures the water contact angle (WCA) of different nanoparticles to determine the hydrophobicity / hydrophilicity of their surfaces. When the contact angle is close to 90°, the particles have the same affinity for the oil phase and the water phase, and tend to be strongly adsorbed at the oil / water interface. When θ<90°, the particles are mainly hydrophilic, and when θ>90°, the particles are mainly hydrophobic. Before embedding, the contact angle of WNPI was 98.4°. After embedding, the contact angle of WNPI / PGA-CA nanoparticles first decreased and then increased. When the ratio of WNPI / PGA:CA was 4:1, the contact angle was the smallest at 33.0° ( Figure 2 ). The presence of chlorogenic acid suppressed the surface hydrophobicity of the protein, and this result indicated that the WNPI / PGA-CA nanoparticles had good hydrophilicity.
[0064] EE and LC of WNPI / PGA-CA nanoparticles for chlorogenic acid: EE (encapsulation efficiency) and LC (loading capacity) are important indicators for measuring the bioactive loading performance of carriers. Figure 3As shown. When the ratio of CA (chlorogenic acid) to WNPI / PGA is 4:1, it shows a higher EE. As the concentration gradually increases, the EE of the nanoparticles first increases and then decreases. This is because excessive CA will cause protein aggregation and cannot successfully enter the hydrophobic region of WNPI, so it cannot be encapsulated by WNPI-PGA. CA is mainly loaded into WNPI-PGA through hydrophobic interactions. The loading capacity (LC) of CA increases with increasing concentration, indicating that the water solubility of natural pigments has been effectively improved.
[0065] Thermal stability of WNPI / PGA-CA nanoparticles: The average particle size and PDI value of the four nanoparticles treated at different temperatures, as well as the retention rate of chlorogenic acid, showed specific changes. With the increase of temperature, the particle size of all nanoparticles first increased and then decreased, among which WNPI / PGA-CA 12:1 The particle size of the WNPI / PGA-CA nanoparticles was always smaller than that of the other three groups. When the temperature reached 95°C, the particle size of all groups decreased significantly. This is because WNPI denatured at high temperature and its tertiary structure dissociated, causing the internal non-polar amino acids to move to the protein surface, thereby promoting hydrophobic interactions and disulfide bond formation between WNPI molecules, and ultimately causing aggregation. 12:1 The PDI value of WNPI-PGA-CA increases significantly with temperature, while 4:1 The PDI values of WNPI-PGA-CA decreased with increasing temperature, but the retention rate of chlorogenic acid decreased with increasing temperature. 4:1 More chlorogenic acid was retained at the same temperature, which may be due to its smaller particle size and more uniform distribution, which helps to maintain the content of chlorogenic acid. These results show that in order to maintain the stability of the system, the best way to store nanoparticles is to store them in a refrigerated state or after high temperature treatment.
[0066] Freeze-thaw stability of WNPI / PGA-CA nanoparticles: Effects of freeze-thaw on the average particle size, PDI, and retention of chlorogenic acid of the four nanoparticles. After freezing, the average particle size and PDI of the four nanoparticles increased slightly. In particular, WNPI / PGA:CA 6:1 The average particle size of WNPI / PGA:CA changed significantly before and after freeze-thaw, from 550.22±8.774nm to 951.82±6.1962nm. Although the PDI value increased, the change was not significant, indicating that freeze-thaw had little effect on the dispersibility of nanoparticles. 12:1 The PDI value of WNPI / PGA:CA was always lower than 0.3, indicating that it maintained good dispersibility after freezing and thawing. 3:1The retention rate of WNPI / PGA:CA was significantly higher than that of the other three groups (79.6±1.1%). This may be because the loose structure of WNPI makes it easy for ice crystals formed during freezing to destroy its structure, increasing the instability of the nanoparticles. However, the increase in CA increased the interaction strength with WNPI, forming a tighter shell structure and reducing the adverse effects of ice crystals. This shows that WNPI / PGA:CA 4:1 It maintains good stability in freeze-thaw state, enhancing its potential for application in frozen foods.
[0067] pH stability of WNPI / PGA-CA nanoparticles: The properties of nanoparticles are highly dependent on pH. At pH 4, the extensive aggregation of WNPI nanoparticles indicates that it is unstable and the average size is significantly increased. According to previous studies, WNPI is unstable at pH 4 and precipitation occurs, but the composite nanoparticles remain stable at pH 4 despite the increase in particle size. This phenomenon indicates that due to the presence of WNPI / PGA, the composite nanoparticles have a denser structure and can resist particle aggregation at pH 4. Different pH values change the magnitude of electrostatic interactions and affect the physical stability of the composite nanoparticles. At pH 2, the PDI of the composite nanoparticles is close to 0.25, indicating that the composite nanoparticles have excellent anti-aggregation stability in the pH range far from the isoelectric point, which may be mainly attributed to the enhanced electrostatic repulsion between particles. At pH values above 4, the PDI increases significantly, indicating that the dispersibility of the nanoparticles deteriorates in alkaline environments. At pH 6, the retention rate of chlorogenic acid for the three nanoparticles reaches the highest, but the retention rate decreases in more alkaline environments. This is because chlorogenic acid is more stable under acidic conditions. When the pH value drops below 4, close to the isoelectric point of walnut protein isolate, the stability of the nanoparticles is impaired, resulting in the exposure of chlorogenic acid and a significant reduction in its content. 4:1 Its stability can be better maintained when used in a weakly acidic environment.
[0068] Temperature storage stability of WNPI / PGA-CA nanoparticles: After 30 days of refrigeration (4°C), WNPI / PGA:CA 12:1 The average particle size of WNPI / PGA:CA expanded from 213.52±6.61nm to 775.73±4.68nm. 4:1 The particle size of WNPI / PGA:CA increased from 469.13±7.81nm to 783.41±8.81nm. 4:1 The PDI value (0.348) is higher than that of WNPI / PGA:CA 12:1 (0.394) is smaller, indicating that the particle distribution of the former is more uniform and stable. Under the same refrigeration conditions, after 30 days, WNPI / PGA:CA 4:1The chlorogenic acid retention rate reached 71.21±0.2%, which was significantly higher than that of WNPI / PGA:CA 12:1 After storage at 25℃ for 30 days, WNPI / PGA:CA 12:1 The particle size of WNPI / PGA:CA increased from 213.52±6.61nm to 827.32±1.15nm. 4:1 The particle size of WNPI / PGA:CA increased from 284.1±7.3nm to 823.58±110.37nm. 12:1 The PDI value rose to 0.384, while WNPI / PGA:CA 4:1 The WNPI / PGA:CA 4:1 67.98±0.50% of chlorogenic acid was retained, which was higher than WNPI / PGA:CA 12:1 These results show that WNPI / PGA:CA 4:1 Improved stability and higher retention of chlorogenic acid were demonstrated, demonstrating that low-temperature storage may help extend the shelf life of nanoparticles.
[0069] Light stability of WNPI / PGA-CA nanoparticles: WNPI / PGA:CA after light exposure 12:1 、WNPI / PGA:CA 6:1 、WNPI / PGA:CA 4:1 and WNPI / PGA:CA 3:1 The retention rates of chlorogenic acid in nanoparticles were 60.4%, 65.21%, 81.53% and 72.43%, respectively. 4:1 It exhibits better photostability because the protein shell encapsulating CA acts as a physical barrier to light and secondly, the aromatic amino acid residues and double bond functional groups of walnut protein isolate are able to absorb light.
[0070] Preparation of PVA-WNPI / PGA-CA composite membrane
[0071] Polyvinyl alcohol (PVA) powder was dissolved in deionized water and heated and stirred at 50°C for 240 min to obtain a 5% (w / v) PVA solution. 4:1 Nanoparticles serve as membrane matrix. The formulation of the membrane-forming solution is as follows (Table 2)
[0072] Table 2 Formulation of PVA-WNPI / PGA-CA nanoparticle film-forming solution
[0073]
[0074] Note: After mixing PVA, WNPI / PGA-CA, and CA, add ultrapure water to make up to 100 mL and then add Tween and glycerol.
[0075] Glycerol was added as a plasticizer and Tween-80 as an emulsifier. All film-forming solutions were stirred at 500 rpm at room temperature (10-25°C) for 60 minutes. The prepared film-forming solution was placed in a 4°C refrigerator for one night to defoam and remove any residual air. 15 mL of the film solution was spread on a plastic culture dish with a diameter of 9 cm. In order to maintain the uniformity of the film, the surface area, volume and drying environment remained unchanged. All films were dried in an incubator at 37°C and 50±2% relative humidity for 10 hours. After cooling, the film was peeled off and placed in a desiccator (relative humidity of 53%) for at least 12 hours at room temperature to obtain a walnut protein antibacterial biofilm.
[0076] Example 2 Structural Characterization of PVA-WNPI / PGA-CA Film
[0077] Microstructure of the film: SEM images of the cross-sectional area of pure PVA film, PVA-CA film and different types of PVA-WNPI / PGA-CA films. Figure 4 As shown. All films except PVA-CA showed discontinuity in the form of micropores or cavities. The presence of these micropores may be related to the evaporation of glycerol during the film formation (drying) process. In addition, with the increase in the concentration of bioactive compounds, a certain amount of glycerol and Tween were added to the film, and pores or cavities appeared, forming an amorphous structure with vacuoles and cavities distributed along the fracture surface, which may correspond to oil droplets, destroying the continuous structure of the membrane matrix to a certain extent.
[0078] Mechanical strength of the film: The mechanical properties of the film are shown in Figure 5 , pure PVA film has high elongation at break (257.78%) and low tensile strength (37.25MPa), showing typical ductile behavior. With the addition of CA, the tensile strength of PVA-CA film increased to 89.42MPa while the elongation at break decreased to 103.96%, which may be because the addition of CA increased the rigidity and brittleness of the coaxial nanofiber film. The interaction between phenolic-protein reduced the effect of plasticizer on the film, thereby increasing the rigidity of the film. However, after the addition of WNPI / PGA-CA nanoparticles, the tensile strength of the film gradually decreased, while the growth rate at break increased significantly, maintaining at around 225.39%, which is because the carboxyl groups of WNPI and the hydroxyl groups of CA form hydrogen bonds, which enhance the interaction between walnut protein isolate molecules. These interactions help to form a denser structure, thereby improving the tensile strength of the nanofiber film.
[0079] FTIR analysis of films: Fourier transform infrared spectroscopy is used to understand the molecular interactions and structural changes of the film at the molecular level. FTIR spectra of PVA films with CA and WNPI / PGA-CA added. The characteristic peak of PVA film is about 3281cm -1 (OH stretching), 2928cm -1 (CH stretch), 1029cm -1 (CO stretching). All developed films showed similar peaks with different amplitudes, and no additional peaks were observed in the bioactive blend films, confirming that no new covalent bonds were formed between the control and blend films. The first peaks of all films fell between 3282 and 3298 cm -1 The wave number of pure PVA film is the highest, which is 3298cm -1 , with the least hydrogen bonds. PVA-WNPI / PGA-CA II and PVA-CA have the lowest wavenumber (3282cm -1 ), the intermembrane hydrogen bonding interaction is the largest, which may be due to the increase of free OH groups, which cannot interact with the polymer matrix. The second peak is at 2914-2926 cm -1 1730~1720cm -1 The peak at 1085 cm indicates C=O stretching. There is no significant difference in C=O vibration between different films. -1 , indicating the stretching vibration of CO. The characteristic peaks of PVA were observed in the films of all samples, indicating that the addition of WNPI / PGA-CA nanoparticles into the PVA matrix did not change the molecular structure of PVA.
[0080] XRD analysis is often used to identify the crystal structure of thin films. The PVA film shows a strong peak at 2θ = 19.3° (indicating the crystalline region), while two weaker diffraction peaks are observed at 2θ = 11.3° and 40.6° (representing the amorphous region), indicating that PVA exhibits semi-crystalline characteristics. After the addition of CA, the intensity of the diffraction peak at 2θ = 19.7° becomes stronger, which is due to the crystalline nature of CA, indicating that the blended material has stronger amorphous characteristics. When PVA is compounded with WNPI / PGA-CA nanoparticles, the intensity of the diffraction peak at 2θ = 19.3° of the composite film becomes weaker. The intensity of the diffraction peak can reflect the morphology of the crystal grains in the crystalline region. Generally speaking, the larger the crystal grains, the higher the intensity of the diffraction peak. Therefore, the addition of nanoparticles reduces the crystallinity of the film matrix, which is attributed to the hydrogen bonds formed by PVA and WNPI / PGA-CA nanoparticles, which destroy the original arrangement of PVA. There are strong intermolecular and intramolecular hydrogen bonds between PVA and CA.
[0081] Rheological analysis of the film: Viscosity changes can reflect the effect of shear on the entanglement structure between molecules; medium viscosity film-forming solutions are considered ideal, because lower or higher viscosities may lead to the formation of uneven films. The network structure formed by a large number of hydroxyl groups and amino groups in PGA molecules exhibits a certain viscosity, and the shear thinning characteristic is mainly due to the destruction of this network structure by the rapid shear process. Figure 6 As shown in the figure, after adding WNPI / PGA-CA to the solution, an increase in solution viscosity was observed, indicating that the polymer network in the solution was strengthened. This strengthening was mainly due to the electrostatic interaction and hydrogen bonding between WNPI, PGA and CA. As the concentration of WNPI / PGA-CA increased, its interaction with PVA became more significant, resulting in a further increase in the viscosity of the film-forming solution. The viscosity analysis results show that the electrostatic interaction and hydrogen bonding between the PVA film matrix and WNPI / PGA-CA strengthened the polymer network structure in the film-forming solution.
[0082] Water vapor and oxygen barrier properties of the film: With the addition of WNPI / PGA-CA, the WVP (water vapor transmission rate) of the PVA film increased from 0.46×10 –6 g / m·s·Pa decreased to 0.38×10 –6 g / m·s·Pa, OP (oxygen permeability) of PVA film is 1.11×10 –2 g / m·s decreased to 0.79×10 –2 g / m·s. First, the reduction of WVP and OP is related to the spatial structure of the film. WNPI / PGA-CA is dispersed in the membrane matrix, and the hydrogen bonds formed with PVA reduce the availability of hydrophilic groups, thereby limiting the water and oxygen absorption capacity of the membrane. At the same time, water molecules pass through the film in three stages: adsorption, diffusion, and decomposition, which means that the hydrophilicity of the film also has an important influence on WVP.
[0083] The surface morphology of the film: Figure 7As shown in the figure, all films have a certain degree of transparency and a smooth surface without dents, uniform pores, wrinkles, bubbles or cracks. The PVA film itself is almost colorless and transparent. With the gradual addition of WNPI / PGA-CA, the film showed a yellow-brown color, which is mainly due to the inherent color of WNPI. With the increase of the WNPI / PGA-CA ratio, the depth of the yellow-brown color gradually deepened. However, when the addition ratio of WNPI / PGA-CA is high, the film covers part of the leaf texture, slightly affecting the visual observation of the food in the package. Table 3 lists the data of the chromaticity value, total color difference (ΔE) and thickness of each group of films. Compared with pure PVA film, PVA film with added WNPI / PGA-CA showed higher L value and b value, which indicates that the transparency of the film gradually decreases and shows a more yellow trend, which is consistent with the appearance change of the composite film.
[0084] Table 3 Film thickness and color parameters
[0085]
[0086] Film thickness is an important parameter of the film, which is related to the mechanical properties, air permeability and light transmittance of the film. As can be seen from Table 3, the thickness of all films ranges from 0.100 to 0.167 mm. Compared with PVA film, the film thickness is significantly enhanced with the increase of CA and WNPI / PGA-CA addition (P<0.05).
[0087] like Figure 8 As shown, all films exhibited a high transmittance mode, but there were significant differences in the film transparency values. Among the films, the PVA-WN PI / PGA-CA II blended film had the lowest transparency, and the pure PVA film exhibited the highest UV transmittance. When the WNPI / PGA-CA content increased, the transmittance of the film gradually decreased. In the range of 200nm-390nm for the PVA-WNPI / PGA-CA II film, the UV transmittance of the film was almost 0. The results of the study indicate that the PVA-WNPI / PGA-CA II film exhibits strong UV and visible light barrier properties, which helps prevent oxidation and deterioration of food in the package due to light exposure.
[0088] Film morphology: The antioxidant activity of pure PVA film is low. When the film concentration is 12.5 mg / mL, its scavenging efficiency for DPPH and ABTS free radicals is only 3.59% and 2.72% (see Fig. 9). With the increase of WNPI / PGA-CA content, the free radical scavenging ability and antioxidant performance of the film were significantly enhanced, which was attributed to the increase of antioxidant content and the expansion of the interaction area between the reagent and the film, proving that the antioxidant capacity of all film samples showed a dose-related enhancement effect. The results show that in PVA-WNPI / PGA-CA film, the excellent antioxidant capacity of the film mainly comes from the antioxidant activity of CA, which can scavenge free radicals through aromatic structure and single electron donor.
[0089] Antibacterial analysis of film: Fig.10 The antibacterial properties of the five groups of films against Gram-positive (Staphylococcus aureus) and Gram-negative (Escherichia coli) bacteria were shown. The absorbance of the bacterial suspension of S. aureus and E. coli of the PVA film without CA loading increased, indicating that PVA had no antibacterial activity. When CA and WNPI / PGA-CA nanoparticles were added to the PVA film, the absorbance of the bacterial suspension of the film decreased to varying degrees, indicating that CA loading had an inhibitory effect on S. aureus and E. coli. However, the antibacterial differences of all CA-loaded films against S. aureus and E. coli were small. The antibacterial ability of PVA-WNPI / PGA-CA II film was slightly greater than that of the other groups. The antibacterial activity of the film was related to the CA content and the distance of CA from the inside of the fiber to the surface. The results showed that loading WNPI / PGA-CA can make PVA-based films have a certain antibacterial effect on S. aureus and E. coli, and can be used as a potential active food packaging material.
[0090] Example 3 Application of PVA-WNPI / PGA-CA composite film in refrigerated storage of fresh pork
[0091] Preparation of pork samples: Fresh pork was purchased in the local market (Kunming, Yunnan, China), and the hind leg meat was taken, the tendons were removed and cut into equal-sized pieces (3×3×1.0 cm), rinsed with pre-cooled deionized water and wiped dry. The pork pieces were randomly divided into 5 groups, placed in sterile culture dishes (90 mm×90 mm), and sealed with PVA film, PVA-CA film, PVA-WNPI / PGA-CA I film, PVA-WNPI / PGA-CA II film, and PVA-WNPI / PGA-CA III film, respectively. Then the sealed test samples were placed in trays and placed in a 4°C constant temperature refrigerator for cold storage. On the 0th, 2nd, 4th, 6th, and 8th days of storage, samples were randomly selected from each group for quality evaluation.
[0092] Effect of film on pork color: Color is one of the most important quality parameters that determine the quality of fresh meat. Therefore, measuring the change in color during storage is a crucial step, so in the present invention, the changes in brightness, chromaticity and hue are monitored by using L*, a*, and b* values. Chromaticity is an important parameter for measuring the color of fresh meat. It measures the color saturation of pork samples. A higher a* value indicates that the pork is relatively fresh; a higher b* value indicates that the pork has deteriorated. During storage, the surface color of pork changes. The brightness of all samples decreased, but the brightness of pure PVA film decreased the most, indicating that the gloss of pork decreased after the storage period. In addition, the oxidation of myoglobin to oxygenated myoglobin is the main factor leading to the decrease in a*. In the middle and late stages of storage (4-8d), the a* of PVA-WNPI / PGA-CA II was significantly higher than that of other groups (P<0.05), indicating that WNPI / PGA-CA inhibited myoglobin oxidation, which may be related to the antioxidant properties of WNPI / PGA-CA. The change in b* value is related to lipid oxidation. The b* value of PVA-WNPI / PGA-CA II was lower than that of the other groups, which may be due to the fact that WNPI / PGA-CA nanoparticles inhibited lipid oxidation in the muscle. It can be seen that the addition of WNPI / PGA-CA has a certain effect on delaying the color change of pork. From all the results, the spoilage rate of pork in the PVA-WNPI / PGA-CA II group was significantly lower than that of the other two groups, so PVA-WNPI / PGA-CA II has the strongest effect on the delayed preservation of pork.
[0093] Effect of film on pH of pork: The pH values of all samples changed as Fig.11 As shown. The pH value of fresh pork before storage was 7.25. During storage, the pH values of each treatment group showed the same trend of change, showing a trend of first decreasing and then increasing. The initial decrease in pH was related to the lactic acid and phosphoric acid produced by anaerobic glycolysis and ATP degradation, and the increase in pH in the later period was due to the accumulation of alkaline compounds. In the early stage of storage (0-2d), the decrease in pH may be due to the decomposition of glycogen by fresh pork under anaerobic conditions to produce acids such as lactic acid. During the storage process of 4-8d, the protein in the pork may be metabolized and degraded into alkaline nitrogen-containing small molecules by microorganisms and proteases, resulting in an increase in pH. In addition, at 4-8d, the pH value of the group loaded with CA was lower than that of the other two groups, indicating that the membrane containing CA prevented the deterioration of the quality of fresh pork to a certain extent. However, since pH is affected by microbial metabolites (such as lactic acid), pH is a reliable indicator of changes in pork quality.
[0094] Effect of film on pork TVB-N (volatile basic nitrogen): TVB-N refers to ammonia and amino nitrogen substances produced by protein decomposition under the combined action of endogenous enzymes and bacteria in the muscle during the storage of animal food. It is one of the important indicators to measure the degree of spoilage of meat products. Fig.12 As shown. The initial TVB-N value of fresh pork was 5.27±0.067 mg / 100g. The TVB-N value of the PVA group reached the maximum on the 8th day, with a value of 23.64±0.643 mg / 100g, while the TVB-N value of the PVA-WNP / PGA-CA II film on the eighth day was the smallest compared with the other five groups, with a value of 14.58±0.087 mg / 100g. With the extension of storage time, the TVB-N value increased to varying degrees, indicating that the quality of pork muscle decreased. On the 8th day of storage, the TVB-N of pork in the pure PVA film exceeded the limit of 20 mg / 100g specified in GB 2733-2015. It shows that WNPI / PGA-CA nanoparticles effectively extend the acceptable freshness period of fresh pork and inhibit the accumulation of TVB-N, which is reflected in the increase of pH value in the later stage of storage. These results may be due to the limitation of protein degradation and microbial growth by CA, similar to the results of nanoemulsion-based edible coatings containing anise essential oil for the preservation of pork patties.
[0095] Effect of film on pork texture: The texture of pork products has a great influence on consumer acceptance. In the process of refrigerating pork, it is very necessary to keep it fresh and tender. At the same time, texture characteristics are an important indicator for measuring pork quality. The present invention measures the hardness, elasticity, resilience, chewiness, cohesion and adhesion of each group of pork during storage. With the extension of storage time, the texture of each group of pork during storage shows a downward trend. This is due to the oxidation of pork tenderloin protein, which leads to intramolecular / intermolecular protein cross-linking through disulfide bonds and non-disulfide bonds, resulting in protein aggregation and formation of complexes, and microbial activity promotes this process. Among them, the pure PVA film has a large change range and serious texture deterioration, while the PVA-WNP / PGA-CA II film may slow down the trend of texture deterioration by inhibiting the activity of microorganisms during storage. This is mainly because the PVA-WNP / PGA-CA II film exhibits better water vapor barrier properties and stronger antioxidant activity than the pure PVA film, thereby more effectively reducing the weight loss of pork and preventing protein oxidation.
[0096] Effect of films on pork microorganisms: All sample groups including PVA, PVA-CA, PVA-WNPI / PGA-CA I, PVA-WNPI / PGA-CA II and PVA-WNPI / PGA-CA I films were stored at 4°C ( Fig.13). Bacterial colonies on pork from each group were collected and observed using the plate count method. Although the types and numbers of bacterial colonies were not studied, the density of bacterial colonies on the agar plate can indicate the ability of the membrane sample to inhibit the reproduction of microorganisms. On the 8th day, both the PVA and PVA-WNPI / PGA-CA membrane groups had a large number of colonies, and the number of colonies in pork packaged with PVA film was greater than that in the control group. The inhibitory effect of PVA-WNPI / PGA-CA II film on the reproduction of microorganisms in fresh pork was more significant than that of the pure PVA film group, which is closely related to the antibacterial ability of CA. After 6 days of storage, the TVC of PVA reached 7.61log 10 CFU / g, exceeding the 7log recommended by the International Committee on Microbiological Standards for Foods 10 CFU / g. This indicates that the addition of WNPI / PGA-CA nanoparticles can effectively inhibit the growth of pork microorganisms, while PVA-WNPI / PGA-CA II film can prolong the growth time of pork microorganisms (at least 8 days)
[0097] The PVA-WNPI / PGA-CA II membrane has a broad-spectrum antibacterial ability, which mainly depends on the antibacterial activity of WNPI / PGA-CA.
[0098] The above are only preferred embodiments of the present invention, and the protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, any modification, equivalent replacement or improvement without departing from the principle of the present invention should be regarded as the protection scope of the present invention.
Claims
1. A method for preparing a walnut protein isolate antibacterial biofilm, characterized in that: The preparation method comprises the following steps: Step (1) mixing a WNPI stock solution and a PGA stock solution, stirring to prepare a WNPI / PGA complex coacervate; Step (2) slowly adding the CA stock solution into the WNPI-PGA complex coacervate solution, stirring in the dark to obtain the WNPI / PGA-CA complex coacervate; Step (3) The PVA solution and the WNPI / PGA-CA complex coacervate are mixed and stirred, refrigerated overnight, and then dried and cooled, and then balanced in a dryer to obtain a walnut protein isolate antibacterial biofilm.
2. The method for preparing the walnut protein isolate antibacterial biofilm according to claim 1, characterized in that: The mass ratio of WNPI to PGA is 1.5-3:1, and the total concentration of the two in the reaction system reaches 0.4-1.0% (w / v).
3. The method for preparing the walnut protein isolate antibacterial biofilm according to claim 1, characterized in that: The mass ratio of WNPI / PGA to CA is 2-8:1; The concentration of CA in the CA stock solution is 0.3-1.0% (w / v); the CA stock solution is slowly added to the WNPI-PGA complex coacervate solution to adjust the final concentration of CA to 0.05%-0.20% (w / v).
4. The method for preparing the walnut protein isolate antibacterial biofilm according to claim 1, characterized in that: In step (1), 0.5-1.5 mol / L hydrochloric acid is used to adjust the pH of the reaction system to 3.0-6.0; the reaction temperature is 2-8°C.
5. The method for preparing the walnut protein isolate antibacterial biofilm according to claim 1, characterized in that: Step (2) using 0.5-1.5 mol / L hydrochloric acid to adjust the pH of the mixed solution to 3.0-6.0, then stirring for 20-60 minutes in the dark, and then centrifuging at a low speed of 2500-4000 rpm for 8-20 minutes to remove possible large aggregates and undissolved matter.
6. The method for preparing the walnut protein isolate antibacterial biofilm according to claim 1, characterized in that: In step (3), glycerol and Tween-80 are also added to the reaction system; the concentration of glycerol in the reaction system is 0.5-1.0%; the concentration of Tween-80 in the reaction system is 0.05-0.2%; the concentration of the PVA solution is 3-10% (w / v); the mass ratio of PVA, WNPI / PGA-CA, glycerol and Tween-80 is 3-10: 0.3-1.0: 0.5-1.0: 0.05-0.
2.
7. A walnut protein isolate antibacterial biofilm prepared according to any one of claims 1 to 6.
8. Use of the walnut protein isolate antibacterial biofilm according to claim 7 in the preparation of an antioxidant or an antibacterial agent.
9. Use of the walnut protein isolate antibacterial biofilm according to claim 7 in preparing food preservatives or food packaging bags.
10. The use according to claim 8, characterized in that: The food is meat products, fruit, yogurt or jelly.
Citation Information
Patent Citations
Isolated soy protein-nano silver antibacterial composite membrane and preparation method thereof
CN102816440A
Walnut peptide-chitosan-sodium alginate composite membrane as well as preparation method and application thereof
CN113278187A
Protein hydrolysate-polyphenol-esterified polysaccharide non-covalent cross-linked edible film and preparation method thereof
CN114907623A
Preparation method of walnut shell lignin enhanced polyvinyl alcohol food preservative film
CN118580533A
Edible bio-active films based on chitosan or a mixture of quinoa protein-chitosan; sheets having chitosan-tripolyphoshate-thymol nanoparticles; production method; bio-packaging comprising same; and use thereof in fresh fruit with a low ph
WO2017132777A1